Antecedents influencing entrepreneurial activity and poverty in Nigeria - Bugaje, Idris Bashir (2018)
Despite Nigeria’s high entrepreneurial activities, poverty statistics are still very high (69%). The North West states have the highest level of poverty from a multidimensional approach in which studies so far have failed to view poverty from a multidimensional angle which reflects a more comprehensive picture of individuals living in poverty. The Nigerian populations are financially excluded with about 65% excluded from the formal financial system. Despite this, there are limited studies on informal sector financing particularly in entrepreneurship while the informal sector in Nigeria is predominant. The available researches on self-efficacy and entrepreneurial capacity rely on its effect on entrepreneurial intention rather than behavior. Furthermore, national culture studies are mainly centered on comparing two or more countries, limited studies compared regions or state in regions in a single country. Given the above, the study seeks to examine the impact of antecedents of entrepreneurial activity on poverty reduction in States in the North –West geopolitical zone of Nigeria. The study samples are three hundred and eighty-seven (387) informal entrepreneurs in North-West Nigeria. Primarily, the study employed the quantitative method which was supported by the qualitative method to enrich the results. Data for the study was collected using questionnaires and interviews. The study found a significant positive relationship between finance availability and entrepreneurial activities. Similarly, even though finances are considered one of the major problems of entrepreneurs, it was however found that the major problem with businesses in distress is related to lack of capabilities. Furthermore, the study revealed a significant negative relationship between entrepreneurial activities and poverty. In light of the findings, the study recommends that finances must be made available to small business for their growth through formal institutions by reducing collateralization, interest rate and the paperwork involved for the informal sector. Thus, group lending should be encouraged to alley fear of defaulters. Similarly, there is a need to have business clinics all over the regions to reduce the number of business failures. Entrepreneurial education and skill training in junior and senior secondary school curricula should be adopted to improve on the capacity of entrepreneurs. Furthermore, in order to increase entrepreneurial activities that will reduce poverty, policymakers should ensure adequate training for informal entrepreneurs and provide accessibility to finances to them. Hence, businesses that are more of opportunity based rather than necessity based should be encouraged. Meanwhile, the differences in the national culture in the states suggest that some states are more entrepreneurial than the others as such policymakers should make policies to improve the entrepreneurial spirit of states with negative culture on entrepreneurship. Policymakers should create awareness to the entrepreneurs on the importance of differentiating between consumption for household and business funds. Policy makers, religious bodies and non-governmental organizations (NGOs) should create awareness or campaign on the challenges of having a very large household, and the potential poverty trap should be emphasized to entrepreneurs and potential entrepreneurs.